PERKECAMBAHAN BENIH PINANG PADA BERBAGAI CARA PENANGANAN BENIH DAN CAHAYA - Sri Mustika; Fathurrahman Fathurrahman; Mahfudz Mahfudz; Muhammad Salim Saleh (Universitas Tadulako, 2010)
The experiment was conducted to assess the influence of various seed handlings in light and without light. Positive contribution in science and technology development is to increase effectiveness and efficiency of areca seed germination. The experiment used a split plot design, with the main plot was light (with and without light) and seed handling as patch (seeds soaked in water for 2, 4, 6 days and seed wetted for 4, 6, 8 days). Each treatment was replicated three times. Data were analyzed using analysis of variance and 5% honestly significant difference. Dark condition accelerated areca seed germination (39.44% growth potential, 93.33% germination rate reached 90 days after planting and 63.33 days to germinate) and increased the number of root and shoot dry weight.